A composite zinc foil based on etching-assisted construction of zinc sulfide protective layer and its preparation method and application
The zinc sulfide protective layer composite zinc foil (ZnS@Zn-ET) prepared through the etch-hydrothermal fusion strategy solves the problem of zinc dendrites and hydrogen evolution corrosion in long-term cycles of aqueous zinc ion batteries, achieving more stable and efficient zinc ion battery performance.
Patent Information
- Application Number
- CN202411332377.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the long-term cycle plating/stripping process, aqueous zinc ion batteries are prone to uncontrollable zinc dendrites and hydrogen evolution corrosion problems, which affects the stability and life of the battery.
Compound zinc foil (ZnS@Zn-ET) based on zinc sulfide protective layer was prepared by etching-hydrothermal fusion strategy. The ZnS protective layer was generated by ultrasonic-assisted in-situ etching and hydrothermal treatment, and the electric field strength of the zinc foil table interface was adjusted to inhibit zinc dendrites and hydrogen evolution.
It effectively suppresses the generation and hydrogen evolution of zinc dendrites in the negative electrode of the aqueous zinc ion battery, extends the service life of zinc metal electrodes, and improves the electrochemical energy storage performance of the battery.
Smart Images

Figure CN119108516B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc ion batteries, and in particular relates to a composite zinc foil based on etching-assisted construction of a zinc sulfide protective layer, and a preparation method and application thereof. Background Art
[0002] The large-scale development of fossil fuels and the rapid development of electric vehicles have brought great pressure to power storage projects. Energy storage is a key link in energy conversion and transmission, and plays a vital role in the sustainable development of industry. As a mature large-scale commercial energy storage device at this stage, rechargeable lithium-ion batteries with outstanding energy density and high voltage platform have always played an irreplaceable role. However, the uneven distribution of lithium resources and the rising cost of lithium have brought great obstacles to the development of lithium-ion batteries. Lithium-ion batteries based on organic electrolyte systems have great safety hazards when short-circuited. Therefore, it is crucial to find alternative energy storage systems. Aqueous zinc-ion batteries have considerable economic benefits, high safety and environmental friendliness, and can be used as promising candidate energy storage devices in some scenarios.
[0003] The redox potential of zinc metal is −0.76 V vs. SHE and the energy consumption is as high as 5855 mAh cm -3 The ultra-high theoretical volumetric energy density and the stability of zinc in water can provide efficient energy storage and high safety for aqueous zinc-ion batteries. The working environment of aqueous zinc-ion batteries is mostly weakly acidic. As an important component of aqueous zinc-ion batteries, the zinc metal anode will produce uncontrollable zinc dendrites and hydrogen evolution and corrosion problems that cannot be ignored during the long-term cyclic electroplating / stripping process. These hidden dangers have brought great challenges to the long-term stable operation of aqueous zinc-ion batteries. At present, the negative electrode interface regulation of zinc-ion batteries has become an important part of optimizing the stability of zinc-ion batteries. It is worth noting that the construction of a suitable interface protection layer on the zinc metal anode can significantly improve these problems. Zinc-based sulfide ZnS can be used as an effective protective layer for the zinc metal anode, and the construction of a hydrophobic interface with an isolation effect helps to inhibit the direct corrosion of the electrolyte on the zinc metal surface. At the same time, the hydrogen evolution phenomenon of the zinc metal anode can also be effectively alleviated. In addition, the electronegative sulfur atoms in the ZnS can effectively regulate the charge distribution during the zinc ion deposition process to guide a more orderly and efficient zinc deposition behavior. Therefore, the composite zinc foil ZnS@Zn-ET based on zinc sulfide protective layer can effectively inhibit the generation of zinc dendrites and hydrogen evolution in the negative electrode of aqueous zinc ion batteries, so as to promote the large-scale application in fields such as aqueous zinc ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a composite zinc foil based on etching-assisted construction of a zinc sulfide protective layer, and a preparation method and application thereof. It is prepared by adopting an etching-hydrothermal fusion strategy, and has a simple process, low cost, scalable preparation, and good electrochemical energy storage performance, providing a new type of nanomaterial for the research and application of electrode materials for aqueous zinc ion batteries.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a composite zinc foil with a zinc sulfide protective layer constructed based on etching assistance, comprising the following steps:
[0007] S1. Polish a piece of zinc foil and protect one side of the polished zinc foil with Kapton tape; add (NH4)2S2O8 powder to deionized water and stir magnetically to a concentration of 0.5 mol L -1 The (NH4)2S2O8 solution is transferred to a culture dish and a piece of zinc foil is placed in the culture dish. The culture dish is placed in an ultrasonic cleaner for ultrasonic-assisted in-situ etching reaction. Through the etching reaction in this process, more zinc active surfaces are exposed, which is beneficial to prevent the aggregation of local zinc dendrites of the original zinc sheet during zinc deposition and help to inhibit zinc dendrites.
[0008] S2. The sample obtained after the etching reaction was rinsed with deionized water to remove excess (NH4)2S2O8, and kept in a vacuum drying oven at 40 ~ 80 ° C for 6 ~ 36 h to obtain a Zn-ET zinc negative electrode;
[0009] S3. Mix deionized water and polyethylene glycol in a 7:1 ratio in a container, and then add K2S powder to the container to a concentration of 0.1 mol L -1 K2S solution;
[0010] S4. The Zn-ET zinc anode and K2S solution were transferred to a stainless steel autoclave lined with polytetrafluoroethylene and kept at 100-150℃ for 6-36h. The etched Zn-ET zinc anode was further hydrothermally treated to generate a ZnS layer on the surface of the Zn-ET zinc anode. The ZnS layer can regulate the Zn content of the zinc foil surface. 2+ The local electric field strength also acts as a protective layer to inhibit zinc foil corrosion, ultimately promoting the orderly deposition of zinc ions and extending the service life of zinc metal electrodes by inhibiting corrosion and alleviating zinc dendrites.
[0011] S5. The zinc foil after the reaction was taken out and rinsed with deionized water, and then kept in a vacuum drying oven at 40 to 80°C for 6 to 36 h to obtain a ZnS@Zn-ET composite zinc negative electrode;
[0012] S6. Use 800 ~ 4000 mesh fine sandpaper to grind the side of the obtained ZnS@Zn-ET composite zinc negative electrode that is not etched by the (NH4)2S2O8 solution to remove the surface ZnS for future use. Since the hydrothermal method will react to generate ZnS on both sides of the zinc foil, the zinc foil on the unetched side is in direct contact with the electrode. This operation is to grind and remove the ZnS on the unetched side to reduce the impact on the experimental results.
[0013] Furthermore, the processing time of the ultrasonic cleaner is 0 to 10 min and the operating frequency is 20 to 80 kHz.
[0014] The zinc sulfide protective layer composite zinc foil ZnS@Zn-ET is prepared by the above preparation method.
[0015] An application of a zinc sulfide protective layer composite zinc foil ZnS@Zn-ET, which is used in the negative electrode energy storage of aqueous zinc ion batteries, can significantly alleviate the zinc dendrite problem of the zinc metal negative electrode of the aqueous zinc ion battery. This is because, firstly, more zinc active surfaces are exposed through etching reactions, which is beneficial to preventing the aggregation of local zinc dendrites of the original zinc sheet during zinc deposition and helps to inhibit zinc dendrites. Then, the etched Zn-ET zinc negative electrode obtained in this process is further hydrothermally treated to generate a ZnS layer in situ on the surface of the Zn-ET zinc negative electrode. The ZnS layer can adjust the Zn on the surface interface of the zinc foil. 2+ The local electric field strength also acts as a protective layer to inhibit the corrosion of zinc foil, ultimately promoting the orderly deposition of zinc ions and extending the service life of the zinc metal electrode by inhibiting corrosion and alleviating zinc dendrites.
[0016] The advantages of the present invention are as follows: the present invention synthesizes a composite zinc foil based on etching-assisted construction of a zinc sulfide protective layer for use as the negative electrode of an aqueous zinc ion battery through an in-situ etching-hydrothermal fusion strategy method. The zinc-based sulfide ZnS can be used as an effective protective layer for the zinc metal negative electrode, and the construction of a hydrophobic interface with an isolation effect helps to inhibit the direct corrosion of the zinc metal surface by the electrolyte. At the same time, the hydrogen evolution phenomenon of the zinc metal negative electrode can also be effectively alleviated. In addition, the sulfur atoms in the electronegative ZnS can effectively regulate the charge distribution during the zinc ion deposition process to guide a more orderly and efficient zinc deposition behavior. Therefore, the composite zinc foil ZnS@Zn-ET based on the zinc sulfide protective layer can effectively inhibit the generation of zinc dendrites and hydrogen evolution at the negative electrode of the aqueous zinc ion battery, so as to promote large-scale applications in the fields of aqueous zinc ion batteries and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The synthetic route of the composite zinc foil ZnS@Zn-ET negative electrode based on the zinc sulfide protective layer in the present invention.
[0018] Figure 21 is the XRD diagram of pure zinc foil, Zn-ET and ZnS@Zn-ET in the embodiments of the present invention.
[0019] Figure 3 This is a SEM image of the surface of the pure zinc foil in the embodiment of the present invention.
[0020] Figure 4 This is a SEM image of the surface of Zn-ET prepared in an example of the present invention.
[0021] Figure 5 This is a SEM image of the surface of ZnS@Zn-ET prepared in an example of the present invention.
[0022] Figure 6 These are the XRD patterns of pure zinc foil, Zn-ET and ZnS@Zn-ET in the embodiments of the present invention after being immersed in 2M ZnSO4 electrolyte solution for 14 days.
[0023] Figure 7 This is a surface SEM image of the pure zinc foil in the embodiment of the present invention after being immersed in a 2M ZnSO4 electrolyte solution for 14 days.
[0024] Figure 8 This is a surface SEM image of the Zn-ET prepared in the example of the present invention after being immersed in a 2M ZnSO4 electrolyte solution for 14 days.
[0025] Fig. 9 This is a surface SEM image of the ZnS@Zn-ET prepared in the example of the present invention after being immersed in a 2M ZnSO4 electrolyte solution for 14 days.
[0026] Fig.10 These are the Tafel curves of pure zinc foil, Zn-ET and ZnS@Zn-ET in 2M ZnSO4 electrolyte solution in the embodiments of the present invention.
[0027] Fig.11 LSV curves of pure zinc foil, Zn-ET and ZnS@Zn-ET in 2M ZnSO4 electrolyte solution in the embodiments of the present invention.
[0028] Fig.12 The pure zinc foil, Zn-ET and ZnS@Zn-ET symmetric batteries in the embodiments of the present invention are shown in Figure 2 at 1 mA cm -2 The area current density and 1 mAh cm -2 Electrochemical deposition / stripping tests at areal capacitance density of .
[0029] Fig.13 The pure zinc foil symmetrical battery in the embodiment of the present invention is 1 mA cm -2 The area current density and 1 mAh cm -2SEM image after 100 cycles at an area capacitance density of .
[0030] Fig.14 The Zn-ET symmetric battery prepared in the embodiment of the present invention has a conductivity of 1 mA cm -2 The area current density and 1 mAh cm -2 SEM image after 100 cycles at an area capacitance density of .
[0031] Fig.15 The ZnS@Zn-ET symmetric battery prepared in the present invention has a conductivity of 1 mA cm -2 The area current density and 1 mAh cm -2 SEM image after 100 cycles at an area capacitance density of . DETAILED DESCRIPTION Example
[0032] A method for preparing a composite zinc foil with a zinc sulfide protective layer constructed based on etching assistance, comprising the following steps:
[0033] (1) First, add an appropriate amount of (NH4)2S2O8 powder into deionized water and stir magnetically to prepare a 0.5 M (NH4)2S2O8 solution;
[0034] (2) transferring the solution obtained in step (1) into a culture dish and placing a piece of commercial zinc foil therein, and then placing the dish into an ultrasonic cleaning apparatus for ultrasonic-assisted in-situ etching reaction;
[0035] (3) The obtained sample was then rinsed with deionized water to remove excess (NH4)2S2O8, and then kept in a vacuum drying oven at 60 °C for 24 h to obtain a preliminary Zn-ET zinc anode;
[0036] (4) Mix 70 mL of deionized water and 10 mL of polyethylene glycol in a beaker with magnetic stirring;
[0037] (5) Add an appropriate amount of K2S powder to the solution obtained in step (4) to a concentration of 0.1 mol L -1 K2S solution;
[0038] (6) The Zn-ET zinc anode obtained in step (3) and the K2S solution obtained in step (5) were transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 120°C for 12 h;
[0039] (7) After the reaction in step (6) is completed, the zinc foil is removed and rinsed with deionized water, and finally kept in a vacuum drying oven at 60°C for 24 h to obtain the final ZnS@Zn-ET composite zinc anode;
[0040] (8) Use fine sandpaper to polish the side of the ZnS@Zn-ET composite zinc negative electrode obtained in step (7) that is not etched by the (NH4)2S2O8 solution to remove the surface ZnS for later use.
[0041] The zinc sulfide protective layer composite zinc foil ZnS@Zn-ET is prepared by the above preparation method.
[0042] Performance Characterization
[0043] The synthesis route of ZnS@Zn-ET zinc anode is as follows Figure 1 The SEM and XRD patterns of the prepared products are shown in Figure 2-9 The electrochemical energy storage performance and the corresponding morphology are shown in Figure 10-15 As shown, specifically, the obtained zinc foil negative electrode ZnS@Zn-ET based on etching-assisted construction of zinc sulfide protective layer was cut into metal discs with a diameter of 12 mm as a battery negative electrode. In the 2M ZnSO4 electrolyte immersion test, ZnS@Zn-ET has an excellent corrosion inhibition effect ( Figure 6-10 );first Figure 6 Figure 2 is the XRD pattern of the electrode after being immersed in 2M ZnSO4 electrolyte solution for 14 days. The results show that the surface of pure Zn and Zn-ET electrode after 14 days of immersion has obvious basic zinc sulfate byproduct ZnSO4(OH)6·H2O, which will seriously affect the deposition behavior of zinc ions. Figure 7-9 The SEM results also show that the pure Zn and Zn-ET electrode surfaces are covered by a large number of basic zinc sulfate nanosheets. In summary, the ZnS@Zn-ET anode modified with a ZnS protective layer has good corrosion inhibition properties. Fig.10 The Tafel curves of pure Zn, Zn-ET and ZnS@Zn-ET in 2M ZnSO4 electrolyte solution in the embodiment of the present invention. The corresponding potential at the tip of each curve corresponds to the corrosion potential of the electrode. The more positive the corrosion potential and the smaller the corrosion current density, the stronger the corrosion inhibition ability. It can be observed that ZnS@Zn-ET exhibits the most positive corrosion potential and the lowest corrosion current density, and has a good corrosion inhibition effect compared to pure Zn. and Figure 6-9 The results are consistent. In addition, ZnS@Zn-ET exhibits excellent ability to inhibit hydrogen evolution compared with pure Zn ( Fig.11 ), Fig.11This curve is used to test the hydrogen evolution ability of the electrode in the electrolyte. It can be seen from the figure that the electrodes all show a certain hydrogen evolution behavior after being lower than -1 V. The hydrogen evolution current density on the vertical axis corresponds to the strength of the hydrogen evolution ability. At the same voltage, the ZnS@Zn-ET electrode shows a smaller hydrogen evolution current density, corresponding to a weaker hydrogen evolution ability, which is beneficial to the battery. In summary, ZnS@Zn-ET has a better ability to inhibit hydrogen evolution. Button cells were assembled using 2M ZnSO4 as the electrolyte for electrochemical testing. The zinc-zinc symmetric battery assembled based on ZnS@Zn-ET also showed better cycle life and more ordered deposition behavior ( Fig.12 ), Fig.12 Cycling curves of symmetric batteries based on pure Zn, Zn-ET and ZnS@Zn-ET in 2MZnSO4 electrolyte solution. Symmetric clicking is often used to simulate the working state of zinc anode (corresponding to the deposition / stripping of zinc ions) to evaluate the cycle life of the electrode. Compared with pure Zn, ZnS@Zn-ET electrode has significantly improved cycle life, which means that this strategy is effective for improving the life of zinc anode. Figure 13-15 The results of pure Zn, Zn-ET and ZnS@Zn-ET symmetric cells at 1 mA cm -2 The area current density and 1 mAh cm -2 SEM image after 100 cycles at an area capacitance density of . The ZnS@Zn-ET negative electrode has a flat surface morphology after cyclic deposition test. The pure Zn surface has the most obvious dendrite aggregation, and the flatness is severely damaged. The figure further illustrates that ZnS@Zn-ET has significantly optimized deposition behavior, which is also the fundamental reason why the electrode has an excellent cycle life.
Claims
1. A method for preparing a composite zinc foil with a zinc sulfide protective layer based on etching-assisted construction, characterized in that: The following steps are involved: S1. Polish a piece of zinc foil and protect one side of the polished zinc foil with Kapton tape; S2. Add (NH4)2S2O8 powder to deionized water with magnetic stirring to a concentration of 0.5 mol L -1 The (NH4)2S2O8 solution is transferred to a culture dish and a pre-treated zinc foil is placed in the culture dish. The culture dish is placed in an ultrasonic cleaner for ultrasonic-assisted in-situ etching reaction. S3. The sample obtained after the etching reaction was rinsed with deionized water to remove excess (NH4)2S2O8, and kept in a vacuum drying oven at 40 ~ 80 ° C for 6 ~ 36 h to obtain a Zn-ET zinc negative electrode; S4. Mix deionized water and polyethylene glycol in a 7:1 ratio in a container, and then add K2S powder to the container to a concentration of 0.1 mol L -1 K2S solution; S5. Transfer the Zn-ET zinc anode and K2S solution to a stainless steel autoclave lined with polytetrafluoroethylene and keep it at 100 ~150℃ for 6 ~ 36h; S6. The zinc foil after the reaction was taken out and rinsed with deionized water, and then kept in a vacuum drying oven at 40 to 80°C for 6 to 36 hours to obtain a ZnS@Zn-ET composite zinc negative electrode; S7. Use 800 ~ 4000 mesh fine sandpaper to grind the side of the obtained ZnS@Zn-ET composite zinc negative electrode that has not been etched by the (NH4)2S2O8 solution to remove the surface ZnS for later use.
2. The method for preparing a composite zinc foil with a zinc sulfide protective layer based on etching-assisted construction according to claim 1, characterized in that: The processing time of the ultrasonic cleaner is 0 to 10 min and the operating frequency is 20 to 80 kHz.
3. A zinc sulfide protective layer composite zinc foil ZnS@Zn-ET prepared according to any one of the preparation methods of claims 1-2.
4. The use of the zinc sulfide protective layer composite zinc foil ZnS@Zn-ET as claimed in claim 3, characterized in that: It is used in negative electrode energy storage of aqueous zinc-ion batteries.
Citation Information
Patent Citations
Film-protected three-dimensional porous zinc negative electrode as well as preparation method and application thereof
CN115663105A
Interface self-welding metal-metal fluoride composite current collector and preparation method thereof
CN118448636A